Applying the IEC-61499 Model to the Shoe Manufacturing Sector - Colla, M.; Brusaferri, A.; Carpanzano, E. (2006 IEEE Conference on Emerging Technologies and Factory Automation, 2006)
This paper presents a new execution model and a concrete application of the IEC 61499 standard in the larger context of a currently running European project, which seeks to preserve shoe-manufacturing activities in Europe through the development of advanced production systems. The present work summarizes an analysis of current practices and research activities in the domain of the design of distributed control systems, and proposes an original design framework made of existing and ad-hoc developed tools, and based on the IEC 61499 standard. As this standard does not prescribe any execution model, we suggest an innovative solution for the implementation level of such distributed control systems. At the end, we present the design choices and some experience gained using the IEC 61499 standard for the design of the automation system of a real plant.